The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10877-016-9956-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pneumotachography and anemometery for flow measurement during mechanical ventilation with volatile anesthetics

Abstract: Volatile anesthetics alter the physical properties of inhaled gases, such as density and viscosity. We hypothesized that the use of these agents during mechanical ventilation would yield systematic biases in estimates of flow (V̇) and tidal volume (VT) for two commonly used flowmeters: the pneumotachograph (PNT), which measures a differential pressure across a calibrated resistive element, and the hot-wire anemometer (HWA), which operates based on convective heat transfer from a current-carrying wire to a flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…However, the degree of the impact of this phenomenon in clinical settings remained unclear. The results of our study were generally consistent with those of previous studies [5,6]. Additionally, our results indicate two important findings: First, the true TV of the lung decreased with an increase in respiratory gas density during PCV as expected, in both laboratory and clinical settings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the degree of the impact of this phenomenon in clinical settings remained unclear. The results of our study were generally consistent with those of previous studies [5,6]. Additionally, our results indicate two important findings: First, the true TV of the lung decreased with an increase in respiratory gas density during PCV as expected, in both laboratory and clinical settings.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, some studies have reported that changes in the respiratory gas composition affect the accuracy of respiratory flow measurements [2,5,6], In this regard, with the progress of anesthesia machines, some anesthesia workstations have integrated gas analyzers and use the information of gas compositions to improve flow and volume monitoring so that TV measured by a built-in pneumotachometer is a closer approximation of the delivered TV. External pneumotachometers with gas 4 analyzers have also been widely used.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies in the literature, different types of anemometers have been used for medical measurement, and results have been compared to flow-meters. [21] Compared to digital drainage systems, the anemometer used in our study has lower sensitivity. We attempted to overcome this technical limitation to a certain extent, by using PALS-PALF values instead of continuous measurements.…”
Section: Discussionmentioning
confidence: 85%
“…To date, some laboratory studies have shown that the gas density in the breathing system influences airway resistance (Mondoñedo et al 2017). Recent clinical studies showed that anesthetic gases, which have higher densities than air and oxygen, increase airway resistance (Habre et al 2001;Nyktari et al 2011).…”
Section: Introductionmentioning
confidence: 99%